On the Doubly Edge Geodetic Number of a Graph - Xavier, D. Antony; Thomas, Elizabeth (International Journal of Computer Sciences and Engineering, 2025)
Geodetic number and its variants is one of the widely studied topic in the field of graph theory. Over the recent years many variants of geodetic number have been extensively studied in the literature. In this paper, we introduce a new variation called doubly edge geodetic number and proved that it is Np-complete. The doubly edge geodetic number for some standard graphs is determined. Furthermore, certain characterization and realization results of doubly edge geodetic number are discussed.